Beyond faith: the transition to inactivity of ministers of religious confession and the emergence of “super-priests” (Revista do Tribunal Regional Federal da 3ª Região, 2025)
The exercise of religious ministry requires full dedication to the spiritual care and moral guidance of the community of believers. However, this intense devotion to the office can lead ministers of religious denominations to disregard their own physical, psychological and age limitations, circumstances which can compromise their ability to work, either temporarily or permanently. Thus, it is essential to recognize the need for social security protection for these professionals, guaranteeing them proper coverage in periods of vulnerability, as well as in the inevitable transition to inactivity. From this perspective, the social security legislation establishes that ministers of religious denominations must be insured under the General Social Security System (RGPS), in the category of individual contributors, considering that the relationship between these professionals and religious institutions does not constitute an employment relationship. On the other hand, considering the context of contemporary dynamics applied to the process of evangelization, it can be seen that ministers of religious confession have started to conduct activities that are dissociated from their eminently priestly attributions. Given this scenario, this study seeks to highlight the need for greater awareness among ministers of religious confession of the effects of this reality on their legal and social security status. Furthermore, the aim is to encourage debate about the need to update the legal system applicable to these ministers, with a view to guaranteeing fundamental rights compatible with the unique nature of their activities.
Keywords: priestly inactivity; retirement of ministers of religious confession; super-priests; need for specific regulations